Planning for Efficient Dispatch - World Bank (World Bank, Washington, DC, 2020)
This study report 'Planning for Efficient Dispatch' was developed within the framework of the project 'Variable Renewable Energy Integration and Planning: Pakistan' under a technical assistance project financed by World Bank in support of the Government of Pakistan. With the aim of being as close as possible to the reality in terms of constraints which cannot be influenced by the dispatcher, potential sources of such deviations have been eliminated in the model. For instance, demand, export to K-Electric, hydrology, VRE output, bagasse output, outages, and nuclearplant operations have been set to their actual historic values. To allow for this analysis and to reach the objectives, the assignment included engagement with the National Power Control Centre (NPCC) as well as technical support. This also included the general topic of VRE integration in support of the wider study.